High Commitment Work System and Employee Proactive Behavior: The Mediating Roles of Self-Efficiency and Career Development Prospect - Shi, Yang; Cao, Man (Frontiers in Psychology, 2022)
Nowadays, proactive behavior has become a major concern in the fields of organizational behavior. Drawing from proactive motivation theory, the paper is proposed the influence of high commitment work system on employees’ proactive behavior, and constructs mediation model including self-efficacy and career development prospect. Moreover, conformity values as a micro context factor is used to illustrate the process that affect employees’ proactive behavior. Analyzing the matched data from 117 enterprises and 1055 employees, the paper is found that high commitment work systems is positively related to employees’ proactive behavior. The paper also is found that self-efficacy and career development prospect are respectively meditated the relationship between high commitment work systems and employees proactive behavior. Conformity value is moderated the positive relationship between self-efficacy and employees proactive behavior, but does not moderate the positive relationship between career development prospect and employees proactive behavior. This study sheds light on whether and how line managers’ leadership influences the HR management process.